Feasibility of using Facebook for HIV prevention: Implications for translational research among justice-involved women who use drugs in rural Appalachia - Michele Staton; Megan F. Dickson; Erika Pike; Sean Young (Journal of Clinical and Translational Science, 2022)
Abstract